Before the new uprooting. Notes for an understanding History of Spanish Dissident Realism: The Case of Roger Wolfe (XXI Century. Spanish Literature and Culture)
This work focuses on a Spanish literary movement, dissident realism, relating it with (apart from the undoubted foreign connections) the tradition of critical realism, a project developed since the postwar years. The article proposes to carry out a reading of dissident realism as an ethical-aesthetic culmination of this critical project and as a postmodern version of the rootless spirit, with special attention to the peculiarities of the individualistic realism, whose main figure is precisely its pioneer: Roger Wolfe.
Keywords: Roger Wolfe; dissident realism; critical tradition; rootless spirit; individualistic aesthetics; postmodernity